Review of the applied mechanical problems in ocean thermal energy conversion. (October 2018) - Zhang, Wei; Li, Ye; Wu, Xiaoni; Guo, Shihao
Abstract: Ocean thermal energy attracted significant attention for its large storage in the ocean. With the increasing exploitation of ocean thermal energy due to the development of technology, several devices were proposed, which can be categorized into the closed cycle, open cycle and hybrid cycle systems. Many researchers have focused on the evaluation of these systems in regard to the economic evaluation, power and efficiency evaluation, function evaluation and environmental impact evaluation. To analyze the performance of such device in the ocean environment, several fluid mechanics problems need to be considered, including steam turbine specific for OTEC system, the wake induced by the long cold water pipe and the turbidity currents on the steep slope. The current work gives a review of these different systems, and presents the power and efficiency calculation formulas. The mechanical applications in the ocean thermal energy conversion (OTEC) system are then discussed. Highlights: Introduces different OTEC systems and working principle. Summarizes existing studies on fluid mechanics problems of OTEC systems. Discusses mechanism of steam turbine and effects of hydrodynamics on CWP. Discusses seakeeping performance of OTEC systems. Discusses effect of environmental factor on OTEC system. Advices on the commercialization of the OTEC systems were proposed.